2011
DOI: 10.1542/peds.2010-2608
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Differences in Use of Intubation for Periviable Neonates

Abstract: Racial/ethnic differences exist in patterns of periviable resuscitation, which may reflect underlying differences in patient preference. Alternatively, institutional practices or resources may account for these differences. These findings have important implications for patient care and institutional practice. Our results lay the foundation for additional work to investigate how social, cultural, and institutional factors influence patient-provider decision-making regarding periviable care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 37 publications
1
18
1
Order By: Relevance
“…Factors that have been implicated in interventions at the limits of viability include maternal age, parity, race, insurance status, education, prenatal care, gestational age, and birth weight [11]. These decisions are often made under inherently stressful circumstances for the affected family and the health care providers who must make the classification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors that have been implicated in interventions at the limits of viability include maternal age, parity, race, insurance status, education, prenatal care, gestational age, and birth weight [11]. These decisions are often made under inherently stressful circumstances for the affected family and the health care providers who must make the classification.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in birth rates of very preterm infants can lead to substantial differences in unadjusted IMRs across demographic groups or regions [5-10]. Approaches to birth classification, resuscitation, and care of the extremely preterm infant may alter outcome and influence the IMR [11]. …”
Section: Introductionmentioning
confidence: 99%
“…There is no legal precedent set for this topic , and consequently, physicians' beliefs regarding neonatal delivery room resuscitation practices of periviable infants vary greatly within the United States (USA) . Factors such as uncertainty of precise gestational age determinations, geographical location, residency training, racial differences and even the apparent devaluation of premature infants by society have all been associated with decisions to resuscitate periviable infants .…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, we have observed racial differences in periviable resuscitation decisions 16 but also found that race was not a predictor of periviable cesarean decisions in the same cohort of infants. 36 It is difficult to know whether the observed racial differences in neonatal intubation reflect variations in patient preferences or provider counselling practices, but the fact that resuscitation differed by race, while mode of delivery did not, suggests that the variation may reflect differences in provider practice.…”
Section: Discussionmentioning
confidence: 64%
“…16,17 Little is known about the source of these differences, although extrapolation from the end-of-life decision-making literature suggests that black and Hispanic patients may have fundamentally different treatment preferences. 1824 An alternative explanation is that ineffective and/or biased patient-provider communication may underlie these differences.…”
Section: Introductionmentioning
confidence: 99%